A zinc-binding site in the largest subunit of DNA-dependent RNA polymerase is involved in enzyme assembly - Markov, Dmitriy (Cold Spring Harbor Laboratory Press, 1999)
All multisubunit DNA-dependent RNA polymerases (RNAP) are zinc metalloenzymes, and at least two zinc atoms are present per enzyme molecule. RNAP residues involved in zinc binding and the functional role of zinc ions in the transcription mechanism or RNAP structure are unknown. Here, we locate four cysteine residues in the Escherichia coli RNAP largest subunit, β′, that coordinate one of the two zinc ions tightly associated with the enzyme. In the absence of zinc, or when zinc binding is prevented by mutation, the in vitro-assembled RNAP retains the proper subunit stoichiometry but is not functional. We demonstrate that zinc acts as a molecular chaperone, converting denatured β′ into a compact conformation that productively associates with other RNAP subunits. The β′ residues coordinating zinc are conserved throughout eubacteria and chloroplasts, but are absent from homologs from eukaryotes and archaea. Thus, the involvement of zinc in the RNAP assembly may be a unique feature of eubacterial-type enzymes.